Efektivitas Pemanfaatan Lahan Pekarangan dalam Mendukung Ketersediaan Pangan pada Era Pandemi Covid-19 di Pedesaan - Reza Asra; Trisnawaty AR (Fapetrik-UMPAR, 2021)
National food security is a problem that must be tackled together, especially in the new normal era caused by the covid 19 pandemic. The yard of the house to produce food is one of the concepts of using yard land both in rural and urban areas to support national food security by empowering potential local food. The yard is not only to create beauty and coolness, but also to improve the economy of each family. The purpose of this study was to determine the characteristics of the community in the use of yard land during the Covid-19 pandemic, to determine the pattern of yard use, and to determine the effectiveness of using yard land in rural areas, especially residents of Carawali Village, Sidrap Regency, in supporting food availability. The data analysis used in this study was an experiment with a one group pre-test post-test design model. In this design, an initial measurement (pre-test) was carried out, after which certain treatment was given, then a re-measurement was carried out (post-test). Sampling in this study using snowball sampling. The results showed that the use of yard land in supporting the food availability of residents in Carawali Village, Watang Pulu District showed that the percentage of the answer scores for the program effectiveness variable described from several questionnaire questions to respondents was in the range of values of 50 - 100%, which means that it is included in the effective criteria.